2023
DOI: 10.3390/toxics11030255
|View full text |Cite
|
Sign up to set email alerts
|

Modeling DNA Methylation Profiles and Epigenetic Analysis of Safflower (Carthamus tinctorius L.) Seedlings Exposed to Copper Heavy Metal

Abstract: Heavy metals are chemical elements with high density that can be toxic or poisonous even at low concentrations. They are widely distributed in the environment due to industrial activities, mining, pesticide use, automotive emissions and domestic wastes. This study aimed to investigate the toxic effects of copper (Cu) heavy metal on safflower plants in terms of genetic and epigenetic parameters. Safflower seeds were exposed to different concentrations of Cu heavy metal solution (20, 40, 80, 160, 320, 640, 1280 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…At high concentrations, heavy metals act as catalysts in the oxidative degradation of biological macromolecules, leading to DNA damage by oxidative stress. Bölükbaşı and Karakaş [ 2 ] exposed Carthamus tinctorius L. (Safflower) seeds to different concentrations of Cu heavy metal solution and reported that high doses of Cu have a genotoxic effect on safflower plants. The presence of a substantial amount of polymorphism in the safflower plants exposed to Cu heavy metal stress was observed, as well as altered DNA methylation patterns, a crucial defence mechanism utilized by the safflower plant.…”
mentioning
confidence: 99%
“…At high concentrations, heavy metals act as catalysts in the oxidative degradation of biological macromolecules, leading to DNA damage by oxidative stress. Bölükbaşı and Karakaş [ 2 ] exposed Carthamus tinctorius L. (Safflower) seeds to different concentrations of Cu heavy metal solution and reported that high doses of Cu have a genotoxic effect on safflower plants. The presence of a substantial amount of polymorphism in the safflower plants exposed to Cu heavy metal stress was observed, as well as altered DNA methylation patterns, a crucial defence mechanism utilized by the safflower plant.…”
mentioning
confidence: 99%